Characterizing Exposure to Physical Risk Factors during Veterinary Surgery with Wearable Sensors: A Pilot Study. Issue 3 (27th October 2022) - Asadi, Hamed; Simons, Micha C.; Breur, Gert J.; Yu, Denny
OCCUPATIONAL APPLICATIONS: Veterinarians provide comprehensive health services for animals, but despite exposure to similar occupational and safety hazards as medical physicians, physical risk factors for these doctors and healthcare teams have not been characterized. In this pilot study, we used wearable sensor technology and showed that veterinary surgeons commonly experience static and demanding postures while performing soft tissue and orthopedic surgeries. Observations showed that muscle activation was highest in the right trapezius. Job factors such as surgical role (attending vs. assisting) and surgical specialty (soft tissue vs. orthopedics) appeared to influence exposure to physical risk factors. These findings suggest a need to consider the unique demands of surgical specialties in order to address the key risk factors impacting injury risks among veterinarians. For example, static postures may be a priority for soft tissue surgeons, while tools that reduce force requirements are more pressing for orthopedic surgeons. TECHNICAL ABSTRACT: Background: Although musculoskeletal fatigue, pain, and injuries are commonly reported among surgeons in veterinary medicine, few studies have objectively characterized the exposure to physical risk factors among veterinary surgeons. Purpose: This study aimed to characterize muscle activation and postures of the neck and shoulders during live veterinary surgeries in the soft tissue and orthopedic specialties. Methods: Forty-four ergonomic exposure assessments (exposures) were collected during 26 surgical procedures across five surgeons. Exposures were collected from both soft tissue ( n  = 23) and orthopedic ( n  = 21) specialties. Physical risk factors were characterized by: (1) directly measuring muscle activation and posture of the neck and shoulders, using surface electromyography and inertial measurement units, respectively; and (2) collecting self-reported workload, pain, and stiffness. Results: Across the 44 exposures, neck and back symptoms respectively worsened after the surgery in 27% and 14% of the exposures. Veterinary surgeons exhibited neck postures involving a mean of 17 ° flexion during the surgical procedures. Static postures were common, occurring during 53–80% of the procedures. Compared to soft tissue procedures (e.g., 13.2% MVC in the right trapezius), higher muscle activity was observed during orthopedic procedures (e.g., 27.6% MVC in the right trapezius). Conclusions: This pilot study showed that physical risk factors (i.e., muscle activity and posture of the neck/shoulder) can be measured using wearable sensors during live veterinary surgeries. The observed risk factors were similar to those documented for medical physicians. Further studies are needed to bring awareness to opportunities for improving workplace ergonomics in veterinary medicine and surgery.